Is Shylock Jewish? : citing scripture and the moral agency of Shakespeare's Jews - Coodin, Sara (Edinburgh critical studies in Shakespeare and philosophy., 2017)
What happens when we consider Shakespearé⁰₉s The Merchant of Venice as a play with ́⁰reaĺ⁰₉ Jewish characters who are not mere ciphers for anti-Semitic Elizabethan stereotypes? Is Shylock Jewish studies Shakespearé⁰₉s extensive use of stories from the Hebrew Bible in The Merchant of Venice, and argues that Shylock and his daughter Jessica draw on recognizably Jewish ways of engaging with those narratives throughout the play. By examining the legacy of Jewish exegesis and cultural lore surrounding these biblical episodes, this book traces the complexity and richness of Merchant́⁰₉s Jewish aspect, spanning encounters with Jews and the Hebrew Bible in the early modern world as well as modern adaptations of Shakespearé⁰₉s play on the Yiddish stage.